INCREASING TEACHER COMPETENCE IN UTILIZING CHROMEBOOKS FOR LEARNING - Tjatur Saban Purnomo; Isna Nurul Inayati (FKDP (Forum Komunikasi Dosen Peneliti), 2023)
The development of science and technology encourages education practitioners to continuously innovate learning in welcoming the industrial era 4.0. Learning in this era requires all elements of education to master 21st century competencies, namely critical thinking, creative, innovative, collaborative and communicative. For this reason, teachers are expected to be able to improve their competence, one of which is in mastering Information and Communication Technology (ICT) in learning. To increase teacher competence in using chromebooks for learning, this school action research will be carried out. This research was carried out at SDN 01 Sidorejo in November 2021 with the research subjects being all 10 teachers at SD Negeri Sidorejo 01. The data collection technique for this school action research is through qualitative data obtained from observation, interviews and document study. This school action research was carried out in 2 cycles. Each cycle includes the following stages: (1) planning, (2) implementation, (3) observation, and (4) reflection. The results of this school action research show that the teacher's ability to use Chromebooks for learning in cycle 1 reached a score of 79.6 and in cycle 2 it was 81.4. The impact of activities on students has shown success with increasing student abilities reaching a score of 85.8 and student wellbeing reaching 88.2. So it can be concluded that increasing teacher competence in using chromebooks for learning can be concluded as successful.